2017
DOI: 10.1177/2050312117721520
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing cardiovascular treatment guidelines application to women and minority populations

Abstract: Despite nearly 30 years of treatment guidelines for cardiovascular diseases and risk factors and a parallel growth in the understanding of cardiovascular disease disparities by sex and race/ethnicity, such disparities persist. The goals of this review are to consider the possible role of three factors: the one-size-fits-all approach of most treatment guidelines, adoption of guideline-recommended treatments in clinical practice, and patient adherence to recommended practice, especially the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Cardiovascular disease (CVD) is one of the leading causes of death in women worldwide including USA and Australia [1,2]. Most of the studies on outcome and increased mortality in women undergoing percutaneous intervention (PCI) has focussed on acute coronary syndromes (ACS), with information on chronic stable angina mostly derived from registries and sub-studies [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiovascular disease (CVD) is one of the leading causes of death in women worldwide including USA and Australia [1,2]. Most of the studies on outcome and increased mortality in women undergoing percutaneous intervention (PCI) has focussed on acute coronary syndromes (ACS), with information on chronic stable angina mostly derived from registries and sub-studies [1].…”
Section: Introductionmentioning
confidence: 99%
“…In patients, presenting with ACS, studies have reported women to suffer increased morbidity and a higher risk of mortality following an index myocardial infarction (MI) event [2][3][4][5]. This has often been attributed to delayed diagnosis, and decreased access to angiography and reperfusion resulting from sex-based disparities in the clinical presentation [6].…”
Section: Introductionmentioning
confidence: 99%